Tenektepláza v liečbe ischemickej NCMP - Nosáľ, Vladimír (Neurologie pro praxi, 2024)
Ischemic stroke is a common and serious condition. Timely restoration of cerebral perfusion is crucial for improving patient outcomes and reducing economic impacts. For three decades, alteplase has been the only established pharmacological treatment, often combined with endovascular therapy. Tenecteplase, a newer generation of fibrinolytic therapy, is recommended by the ESO 2023 guidelines as a suitable alternative to alteplase, particularly if treatment is initiated within 4.5 hours of symptom onset. Tenecteplase offers higher fibrin specificity, lower binding to PAI-1, and a longer plasma half-life compared to alteplase, allowing for single bolus administration. Clinical studies have shown that tenecteplase 0.25 mg/kg achieves better recanalization and clinical improvement without increased risk of bleeding. It is equally effective and safe as alteplase, with meta-analyses indicating improved recanalization and clinical outcomes at a lower risk of bleeding. Tenecteplase is a suitable alternative for treating iNCMP, especially within 4.5 hours of symptom onset. Its single bolus administration simplifies hospital management and improves the logistics of transporting patients to specialized centers.
Keywords: trombolytická terapie; Thrombolytic Therapy; Tissue Plasminogen Activator; Tenecteplase; Clinical Studies as Topic; fibrinolýza; tkáňový aktivátor plazminogenu; klinická studie jako téma; ischemická cévní mozková příhoda; tenektepláza; Reperfusion; lidé; reperfuze; Fibrinolysis; Humans; Ischemic Stroke